MOTIVATION OF EFL STUDENTS AT TERTIARY LEVEL - Dwi Ratnasari (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: This paper discusses about motivation of EFL students at tertiary level. This study used a survey method. The participants of this study were 323 students in a private university in Palembang. A questionnaire assessing motivation was used in this study. A 51-item questionnaire used in this study was an adapted version of Schmidt, Boraie, and Kassabgy’s instrument used in their study. Some of these items were added based on the theory of socio-education (Gardner, 1985, 1988, 2000, 2001; Gardner and MacIntyre, 1991, 1993). The result of this study showed that the main motivational components that underlie the students to learn English are instrumental orientation, intrinsic orientation, and integrative orientation. Key words: motivation, EFL students, tertiary level